Effect of mating on survival at low temperature in females of the Japanese common grass yellow, Eurema mandarina. (20th May 2018) - Konagaya, Tatsuro; Numata, Hideharu
Abstract : In the Japanese common grass yellow, Eurema mandarina, the mean survival period at 10 °C was 13.4 and 7.9 weeks for mated and unmated females, respectively. Morphological changes in the spermatophores removed from mated females suggest digestion of spermatophores by females. This result indicates that adaptive significance of pre‐overwintering copulation of females is acquisition of nutrients for overwintering. Abstract : 1. In some insects that overwinter as adults, mating occurs both before and after overwintering. Two hypotheses have been proposed to explain the adaptive significance of pre‐overwintering copulation of females. One is the bet‐hedging hypothesis, which explains pre‐overwintering copulation as a preparation for less chance of mating in the following spring. The other is the nuptial gift hypothesis, which states that secretions derived from males increase overwintering success of females. 2. In Eurema mandarina, both diapause autumn‐ and non‐diapause summer‐form male adults emerge with autumn‐form female adults in the last generation in a year. Most autumn‐form females mate with summer‐form males before winter, and re‐mate with autumn‐form males in the following spring. Because autumn‐form females have sufficient chances for mating after overwintering, the nuptial gift hypothesis has been regarded as the more probable hypothesis. 3. To test the nuptial gift hypothesis, the survival period was compared under short‐day conditions at 10 °C between mated and unmated females that had been reared on sucrose solution at 25 °C for 15–21 days. The mated females had significantly greater longevity than the unmated females, supporting the nuptial gift hypothesis. Body size also affected the survival period. 4. The results suggest that the nuptial gift is an important factor for the evolution of pre‐overwintering copulation in species in which females mate both before and after overwintering.